Bile acid signaling and biliary functions - Hannah Jones; Gianfranco Alpini; Heather Francis (Elsevier, 2015)
This review focuses on various components of bile acid signaling in relation to cholangiocytes. Their roles as targets for potential therapies for cholangiopathies are also explored. While many factors are involved in these complex signaling pathways, this review emphasizes the roles of transmembrane G protein coupled receptor (TGR5), farnesoid X receptor (FXR), ursodeoxycholic acid (UDCA) and the bicarbonate umbrella. Following a general background on cholangiocytes and bile acids, we will expand the review and include sections that are most recently known (within 5-7 years) regarding the field of bile acid signaling and cholangiocyte function. These findings all demonstrate that bile acids influence biliary functions which can, in turn, regulate the cholangiocyte response during pathological events.